Comparative macrolide use in humans and animals: should macrolides be moved off the World Health Organisation's critically important antimicrobial list?. (6th May 2021) - Trott, Darren J; Turnidge, John; Kovac, Jessica H; Simjee, Shabbir; Wilson, Danny; Watts, Jeffrey
: Macrolide antibiotics are categorized by the WHO as Highest Priority, Critically Important Antimicrobials due to their recommendation as treatment for severe cases of campylobacteriosis in humans; a self-limiting, rarely life-threatening, zoonotic foodborne infection. Low rates of macrolide resistance in Campylobacter jejuni and the availability of alternative treatments have prompted some regulatory schemes to assign macrolides to a lower importance category. Apart from rare, specific infections, macrolides largely play a supportive role to other drug classes in human medicine. By contrast, although the advent of alternative control methods has seen significant reductions in macrolide use in intensive livestock, they still have a crucial role in the treatment/control of respiratory infections and liver abscesses in cattle. Whilst acknowledging that ongoing surveillance is required to reduce the spread of recently emerged, transferable macrolide resistance among Campylobacter, this article recommends that macrolides should be moved to the WHO Highly Important category.